THE INFLUENCE OF FAMILY ENVIRONMENT, SYSTEM EDUCATION, SOCIAL ENVIRONMENT ON STUDENTS’ LEARNING IN UNDERSTANDING LESSON AT HIGH SCHOOL IN CIKARANG - Muhammad Riqi; Aviansyah Chaniago; Hernawati W. Retno Wiratih (President University, 2021)
This study aims to determine the factors that affect the understanding lessons of students at High School in Cikarang. These factors are family environment, education system, and social environment. Students who have a high motivation to learn will have a positive result of their grades and understanding the lesson. This study uses quantitative descriptive and for collecting the data are using questionnaires. In addition, SPSS is utilized to analyze the collected data. The total number of samples was 182 respondents. Sampling design is Probability sampling and the technique using simple random sampling. To check the hypothesis of this analysis, multiple regression analyzes were used. The result of the research shows (1) Family Environment (X1) has positive insignificant influence on Students Understanding Lesson, (2) Education System (X2) has negative influence on Students Understanding Lesson, (3) Social Environment (X3) positive significant influence on Students Understanding Lesson. The coefficient of determination shows that the variable Family Environment (X1), Education System (X2), and Social Environment (X3) influence Understanding Lesson of Student (Y) of 45.7%, while the remaining 54.3% influenced by other variables outside thisresearch.Keywords: Family Environment, Education System, Social Environment, Understanding Lesson of Student